Metallurgia coque applied to catodic protection - Hernández Puerto, Yenny Rubiela (2007)
The metallurgical coke has been known by its applications how reductor and fuel agent in different processes of metals obtaining. The corrosion protection sector makes use of the coke for an application with different requirements to those. Understanding the requirements, the raw incidence and the coke making variables and implementing the certain production process then, it can end up being satisfied this specialized necessity of coke use. This paper present to determination the electrical conductivity of the cokes obtained from different range coal and the addition of coal and petroleum pitches influence, mainly over this property and the optic texture of the make cokes. The pitches addition affects in a different way the electrical conductivity of cokes, depending on the coal range, and the origin and proportions of additives.